ANALISIS PENGARUH KOMPENSASI, MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI INSTALASI FARMASI RUMAH SAKIT UMUM PUSAT FATMAWATI JAKARTA SELATAN - Muniardi Muniardi (Value : Jurnal Manajemen dan Akuntansi, 2020)
In installation environments Jakarta Fatmawati hospital, the level of compensation is still unable to satisfy their existing employees, nor the motivation given by the management company is still lacking, and also the problem of employee discipline that can be categorized as a lack of discipline. Of course, with things like that can affect employee performance, but if the amount is very significant effect or not must be done further research.For studying, this research is conducted with the formulation of the problem as follows: (1) How much influence Compensation for employee performance Installation of Pharmacy in General Hospital Fatmawati, South Jakarta, (2) How much influence work motivation on employee performance Installation of Pharmacy in General Hospital Fitness Fatmawati, South Jakarta, (3) How much influence Work Discipline against employee performance Installation of Pharmacy in General Hospital Fatmawati, South Jakarta (4) How much influence Compensation, Work Motivation and Discipline Working together towards employee performance Pharmacy Installation at Home General Hospital Center Fatmawati, South Jakarta.To answer the problem formulation above, this study was conducted with descriptive correlational design. This research was conducted the hospital pharmacy environment Fatmawati Jakarta with a population of 150 people and a sample of 110 people. Samples taken at random proportional. Collecting data in this study using a questionnaire or a questionnaire as an instrument.The results showed that: (1) Compensation is the independent variable that proved positive and significant effect on the performance of employees by 93%, while the remaining 7% is influenced by other factors. It shows if the compensation increases, performance of employees will increase. (2) Motivation is a free variable that proved positive and significant impact on employee performance of 88.9%, while the remaining 11.1% is influenced by other factors. It shows if the motivation to increase the performance of employees will increase. (3) Discipline is the independent variable that proved positive and significant effect on the performance of employees amounted to 91.6%, while the remaining 8.4% is influenced by other factors. It shows if the discipline increases the performance of employees will increase. (4) Compensation, motivation and discipline simultaneously together significant positive effect on the performance of employees amounted to 96.8%. While the remaining 3.2% is influenced by other variables not examined in this study. Keywords : Compensation, Motivation, Discipline, Performance Officer.